Mrs. Barr has gone too far! - Gutman, Dan; Paillot, Jim (New York Harper, an imprint of HarperCollins Publishers, 2021)
"After noticing that A.J. and his friends' geography knowledge could use some work, Mr. Cooper invites to class just the person to help. Globetrotter Mrs. Barr speaks seven languages and has visited nearly two hundred countries! But why does she carry a suitcase everywhere she goes? And why does she open a window whenever she walks into a room? Perhaps Mrs. Barr has something to hide"--Provided by publisher
110612
Keywords: Elementary schools -- Juvenile fiction; Geography; Travelers; Schools; Humorous stories; Secrets; Children's stories; Chapter books; Humorous fiction; Juvenile works